Afrique du Sud : politique extérieure et rapports avec le continent - Anglin, Douglas (Études internationales, 1991)
The principal preoccupation of South African foreign policy decision makers has consistently been the preservation and perpetuation of white power and privilege. This has been especially the case with respect to relations with the rest of Africa, and above all Southern Africa which South Africa has long regarded as its natural hinterland. Traditionally, the neighbouring states have been a source of minerals, markets and migrant labour, but more recently they have also been perceived as a source of insecurity. Pretoria countered the alleged "total onslaught" it faced with its "total strategy" which, in the region, amounted to a combination ofathump and talk. "The military reverse South Africa suffered in Angola in 1988 forced a reassessment of policy, leading to the independance of Namibia and the prospect of an end to apartheid domestically. How the emergence of a non-racial democratic regime in South Africa will affect policy towards the continent is uncertain. While the African National Congress recognizes the need to put the relationship on a new and mutually beneficial basis, it is likely to be preoccupied with its own formidable domestic agenda. This may leave policy effectively in the hands of the technocrats and the businessmen, which does not augur well for an end to the present exploitative relationship.